SEVERE ACUTE RESPIRATORY SYNDROME (SARS) – A NEW INFECTIOUS DISEASE AND MAIN PROBLEMS OF ITS PROPHYLAXIS IN ASIAN PART OF RUSSIA - G. G. Onishchenko; E. P. Golubinsky; A. D. Botvinkin; A. S. Maramovich; A. M. Titenko; S. A. Kosilko (Acta Biomedica Scientifica, 2020)
Publications, directive and instructionalmethodical papers of WHO, Government and Ministry of Public Health of Russian Federation prepared due to SARS epidemics are reviewed. A brief characteristics of the new disease is represented, the history of the virus discovery, the disease dynamics and SARS dissemination in the world in 2003 are described. Information about SARS suspected cases in Russia and main data on laboratory and clinical epidemiological diagnostics are represented. Measures undertaken for the new disease control are considered in the concluding part of the review. Peculiarities of Siberia and Far East (the region closely connected with the most SARS affected Asian countries) are marked.